Study on Pattern and Prevalence of Dyslipidemia and Other Cardiovascular Risk Factors among the Various Ethnic Groups of Trinidad and Tobago - Idris Saleh; B. Shivananda Nayak (Issues and Development in Health Research Vol. 8, 2021)
Background: Dyslipidemia has consistently been associated to the development of problems such as cardiovascular disease (CVD), and it is a key component of the metabolic syndrome. Furthermore, disparities in the pattern of lipid derangements have been reported, particularly between people of African ancestry and their South Asian counterparts. Aim: The present study aims to highlight the pattern and prevalence of dyslipidemia and other cardiovascular risk factors among the various ethnic groups in Trinidad and Tobago. Materials and Methods: After an overnight fast of 10–12 hours, 10 mL of blood was obtained from each of the 968 patients in this investigation. Glucose, total cholesterol, triglycerides, high density cholesterol (HDL-c), very low density lipoprotein (VLDL), and low density lipoprotein (LDL) were all measured in plasma and sera (LDL). Each subject’s anthropometric indices were measured, including height, weight, waist circumference, age, gender, education, occupation, ethnicity, and medical history, including medications. Results: Our study shows that hypertriglyceridemia was prevalent in 33.88% of the patients with the highest observed prevalence of 46.69% seen in the South Asians. There were differences in body mass index (BMI), systolic blood pressure, blood glucose, triglycerides and very low-density lipoprotein cholesterol amongst the various ethnic groups (p < 0.05). However, levels of HDL-c were similar among the various ethnicities although patients of the South Asian descent tend to have a trend towards none-significantly higher levels of HDL-c compared with other ethnic groups (p > 0.05). Conclusion: The study emphasised the well-known significant disparity in lipid profiles among people of different ethnic groups, particularly among patients with chronic noncommunicable disease (CNCD) in Trinidad and Tobago.